Botyrococcus Braunii Cultivation in the Wet Oxidation Liquid from the Hydrothermal Carbonization of Orange Pomace - Tarhan, Seray Zora; Kocer, Anil Tevfik; Ozcimen, Didem; Gokalp, Iskender (Mehmet Sinan Bilgili, 2020)
Food waste is a worldwide problem that leads to both food scarcities and environmental issues. A very important fraction of food waste is landfilled and constitutes sources of carbon dioxide and methane by anaerobic digestion, contributing therefore to global warming. Hydrothermal carbonization (HTC) is a specific thermochemical conversion process converting very wet organic waste streams to a valuable energy-rich hydrochar. However, the process water issuing from the HTC should also be post treated as it includes high amounts of carbon and several toxic chemicals. In the present study, we treated the aqueous phase of the HTC process by wet oxidation (WO) and we used the resulting liquid as a culture medium for micro algal growth. This method is applied in this study to the process water of HTC treatment of orange pomace which is an organic waste generated in considerable amounts around the world. Botyrococcus braunii was used as the algal strain. The results showed that B.braunii can be efficiently cultivated in the WO liquid, especially for low dilution rates. It has been therefore demonstrated that this integrated approach provides a low cost nutriment medium for algal growth and contributes to the sustainable remediation of the HTC process water.
Keywords: Algal cultivation; Botyrococcus braunii; hydrothermal carbonization; wet oxidation; FOOD WASTE; NUTRIENT RECOVERY; MUNICIPAL SLUDGE; CONVERSION; BIOMASS; HTC; TEMPERATURE; MANAGEMENT; MICROALGAE; PRODUCTS; Engineering; Environmental Sciences & Ecology